Relationships between muscle size, strength, and physical activity in adults with muscular dystrophy. Issue 6 (19th October 2018) - Jacques, Matthew F.; Onambele‐Pearson, Gladys L.; Reeves, Neil D.; Stebbings, Georgina K.; Smith, Jonathon; Morse, Christopher I.
Abstract: Background: Muscular dystrophy (MD) is characterized by progressive muscle wasting and weakness, yet few comparisons to non‐MD controls (CTRL) of muscle strength and size in this adult population exist. Physical activity (PA) is promoted to maintain health and muscle strength within MD; however, PA reporting in adults with MD is limited to recall data, and its impact on muscle strength is seldom explored. Methods: This study included 76 participants: 16 non‐MD (CTRL, mean age 35.4), 15 Duchenne MD (DMD, mean age 24.2), 18 Becker's MD (BMD, mean age 42.4), 13 limb‐girdle MD (LGMD, mean age 43.1), and 14 facioscapulohumeral MD (mean age 47.7). Body fat (%) and lean body mass (LBM) were measured using bioelectrical‐impedance. Gastrocnemius medialis (GM) anatomical cross‐sectional area (ACSA) was determined using B‐mode ultrasound. Isometric maximal voluntary contraction (MVC) was assessed during plantar flexion (PFMVC) and knee extension (KEMVC). PA was measured for seven continuous days using triaxial accelerometry and was expressed as daily average minutes being physically active (TPA mins ) or average daily percentage of waking hours being sedentary (sedentary behaviour). Additionally, 10 m walk time was assessed. Results: Muscular dystrophy groups had 34–46% higher body fat (%) than CTRL. DMD showed differences in LBM with 21–28% less LBM than all other groups. PFMVC and KEMVC were 36–75% and 24–92% lower, respectively, in MD groups than CTRL. GM ACSA was 47% and 39% larger in BMD and LGMD, respectively, compared with CTRL. PFMVC was associated with GM ACSA in DMD ( P  = 0.026, R  = 0.429) and CTRL ( P  = 0.015, R  = 0.553). MD groups were 14–38% more sedentary than CTRL groups, while DMD were more sedentary than BMD (14%), LGMD (8%), and facioscapulohumeral MD (14%). Sedentary behaviour was associated with LBM in DMD participants ( P  = 0.021, R  = −0.446). TPA mins was associated with KEMVC ( P  = 0.020, R  = 0.540) in BMD participants, while TPA mins was also the best predictor of 10 m walk time ( P  < 0.001, R 2  = 0.540) in ambulant MD, revealed by multiple linear regression. Conclusions: Quantified muscle weakness and impaired 10 m walking time is reported in adults with MD. Muscle weakness and 10 m walk time were associated with lower levels of TPA in adults with MD. Higher levels of sedentary behaviour were associated with reduced LBM in DMD. These findings suggest a need for investigations into patterns of PA behaviour, and relevant interventions to reduce sedentary behaviour and encourage PA in adults with MD regardless of impairment severity.